PENERAPAN ALGORITMA MFEP DALAM MEREKOMENDASIKAN MODE HIJAB TERBAIK DIKALANGAN REMAJA - Aningke, Tri; Pradana, Yuni; Facharaini, Nur Ika; Gukguk, Marina Raja (Jurnal Informatika, 2018)
This study aims to develop decision support system in determining the selection of the best hijab mode among teenagers in Pematangsiantar city. The research data is sourced from a questionnaire quiz in the form of a questionnaire of 100 teenagers. The alternatives used are 3 hijab modes and 7 criteria as the best hijab modes assessment among Pematangsiantar city adolescents, ie price criteria (C1), material (C2), size (C3), motif (C4), quality (C5), color (C6 ) and face shape (C7). The research used MFEP (Multi Factor Evaluation Process) method. This developed system shows that the best hijab mode that teenagers use for everyday life is Square Four. With this system, adolescents can choose the best hijab mode that can be used daily in a more objective way.